ROBIN SHARMA'S TRANSLATION INTO UZBEK "WHO WILL CRY WHEN YOU DIE?" LEXICAL-TRANSFORMATIVE TRANSLATION IN HIS WORK (World Bulletin of Social Sciences, 2024)
In this article, the lexical transformative analysis of the English-to-Uzbek translation of Robin Sharman's work "O'lsang kim yigyaldi", one of the bright figures of world literature, is considered, and lexical transformation is also emphasized. . One of the important aspects of the translation process is to collect general information about the work and get to know them, so the following article focuses on the work and the author
Keywords: Translation; lexicon; transformation; morphology